2022
DOI: 10.1038/s41598-022-06811-6
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology-based approach to explore mechanism of action of medicinal herbs for alopecia treatment

Abstract: Hair loss is one of the most common skin problems experienced by more than half of the world's population. In East Asia, medicinal herbs have been used widely in clinical practice to treat hair loss. Recent studies, including systematic literature reviews, indicate that medicinal herbs may demonstrate potential effects for hair loss treatment. In a previous study, we identified medical herbs used frequently for alopecia treatment. Herein, we explored the potential novel therapeutic mechanisms of 20 vital medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Colorectal cancer is the third most commonly diagnosed malignancy worldwide, with significant geographic heterogeneity in incidence and mortality . The combination of network pharmacology and molecular docking technology is gradually forming a systematic paradigm, providing an unprecedented opportunity for the systematic study of traditional medicinal plants in cancer, and becoming a Frontier research field in drug discovery and development. It has been reported that Mufangji decoction, a famous traditional Chinese medicine formula, can treat lung cancer by multiple pathways, multiple targets, and multiple components based on network pharmacology and experimental validation . Gao et al also reported that aloin protects against gastric cancer by regulating the PI3K-AKT signaling pathway through integrating network pharmacology and experimental verification .…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is the third most commonly diagnosed malignancy worldwide, with significant geographic heterogeneity in incidence and mortality . The combination of network pharmacology and molecular docking technology is gradually forming a systematic paradigm, providing an unprecedented opportunity for the systematic study of traditional medicinal plants in cancer, and becoming a Frontier research field in drug discovery and development. It has been reported that Mufangji decoction, a famous traditional Chinese medicine formula, can treat lung cancer by multiple pathways, multiple targets, and multiple components based on network pharmacology and experimental validation . Gao et al also reported that aloin protects against gastric cancer by regulating the PI3K-AKT signaling pathway through integrating network pharmacology and experimental verification .…”
Section: Discussionmentioning
confidence: 99%
“…The SWISS online prediction platform selected the targets with the parameter Probability ≥0.6 in the prediction results for further analysis (Balogh et al, 2022). Superpred predicts the potential targets of unknown molecules by calculating the Tanimoto similarity of the molecule to over 300,000 known compounds in the server (Leem et al, 2022).…”
Section: Prediction Of Potential Targetsmentioning
confidence: 99%
“…In addition, network pharmacology can predict the bioactive ingredients and mechanisms of TCM for the treatment of diseases. Many studies have demonstrated the scientific nature of network pharmacology ( 9 , 10 ). Network pharmacology provides a new research paradigm for evidence-based medicine systems and will accelerate our understanding of TCM.…”
Section: Introductionmentioning
confidence: 99%